Stars and planets: read it yourself with ladybird: level 2 - Horsley, Lorraine (Ladybird London, 2004)
How big is Mars? Which planets are next to Earth? This non-fiction title talks about the wonders of space with accurate charts and illustration, exciting facts about each planet and carefully levelled text for beginner readers.